Analysis of vitamic C content in locally-made orange juice drinks in the Philippines - Quan, Glen Lelyn (Animo Repository, 2006)
Due to the rampant falsified marketing of Vitamin C content among locally-produced orange juice drinks, it is necessary to investigate which brand actually contains the accurate amount of Vitamin C.Volumetric titration technique was employed, involving the redox reaction between a standardized I2 and ascorbic acid solution. Five brands of orange juices were analyzed for their Vitamin C content. The results indicated that the Del Monte brand provides the most amount of Vitamin C, requiring the consumers just 58.37 ml of it to meet the RDA for Vitamin C. The least brand containing is that of Jungle Juice; consumers need to take 497.7 ml of it to meet the RDA. The results obtained provide accurate information against false marketing of Vitamin C content in locally made orange juice drinks.